Seismic Acceleration Spectrum of Ground Surface under Urban Subway Tunnels with Circular Cross Sections in Soil Deposits Based on SSI - Hamed Fakhriyeh; Reza Vahdani; Mohsen Gerami (Shock and Vibration)
Underground tunnels with circular cross section nowadays have great application in the field of transportation. One of their most prominent uses is the subway, built with the help of tunnel boring machines (TBMs). The design of ground-surface structures in the far field is related to the horizontal component of the peak ground of acceleration. Therefore, in this study, we tried to change the frequency of the soil-tunnel system by changing the overburden depth, diameter, and lining thickness of the tunnel, as well as changes in the soil specification, and calculate the maximum acceleration of the ground’s surface in the presence of the tunnel. The relationship between the peak horizontal acceleration of the ground surface and the frequency of the soil-tunnel system will result in the production of a horizontal acceleration spectrum. The results show that the amplification of ground surface depends on the period of the soil-tunnel system, the characteristics of the model, and the status of the point studied at the ground surface relative to the tunnel. On the projection of the center of the tunnel on the surface of the ground, the presence of the tunnel, rarely, at a long period, is effective in amplifying the spectral acceleration. While moving away from the image of the center of the tunnel on the surface of the ground, the presence of the tunnel in many cases, in long periods, amplifies spectral acceleration. The presence of the tunnel amplifies the spectral acceleration on the ground surface above 11%, while the presence of a tunnel reduces the spectral acceleration on the ground surface by up to 15% (attenuation). Using Plaxis 2D and Ansys finite element software, the case study was conducted on a Delhi subway tunnel with horizontal components of acceleration records similar to the construction site.